Triple bagging hermetic technology for post-harvest preservation of paddy rice Oryza sativa L. in the Sahel of West Africa. (July 2016) - Baoua, I.B.; Amadou, L.; Bakoye, O.; Baributsa, D.; Murdock, L.L.
Abstract: Trials of the Purdue Improved Crop Storage (PICS) bag technology for the storage of paddy rice, Oryza sativa L., were conducted in Burkina Faso, Ghana and Niger. Paddy rice naturally infested with insects, the most abundant species being Tribolium spp. and Rhizopertha dominica, was sealed in triple layer PICS bags, or in conventional woven polypropylene sacks. At the end of 7–18 months of storage in PICS bags the number of insects did not increase, the weight of 100 seeds did not change, and the proportion of damaged seeds was not different from that present when the paddy was first put into the bags. By contrast, paddy stored in the conventional way in woven polypropylene bags exhibited weight losses ranging from 3 to 8.7%. In Bolgatanga, Ghana, where paddy was stored for 18 months, germination of paddy kept in the PICS bags was comparable to that present at the beginning of the experiment. PICS bags can be used for the safe, low-cost, insecticide free storage of paddy rice. Highlights: PICS triple bagging technology was tested for storage of paddy rice. Tests were conducted in three West African countries: Burkina Faso, Ghana and Niger. PICS bags stopped grain weight loss and arrested insect population growth. Grain stored in PICS bags germinated as well or better than in woven plastic bags. African-manufactured PICS bags are a low-cost, insecticide-free way to store paddy rice.